Therapeutic Facet Joint Interventions in the Lumbar Spine: An Economic Value Perspective. Issue 10 (December 2020) - Mazmudar, Aditya; Nayak, Rusheel; Patel, Alpesh A.
Abstract : Objective: In this narrative review, the current literature on therapeutic interventions for low back pain of facet joint etiology is assessed from an economic value perspective. Summary of Background Data: The efficacy and economics of facet joint interventions in the treatment of lumbar back pain is a controversial topic. Trends show that facet joint interventions are becoming increasingly used, perhaps as physicians become more averse to treating chronic low back pain with opioids. With the emphasis on value-based spine care and changing reimbursement models, the perspective of rigorously evaluating the outcomes these interventions provide and the costs they incur is particularly relevant. Discussion: Although the evidence is noted to be limited, most systematic reviews fail to demonstrate the therapeutic utility of intra-articular facet joint injections in low back pain because of high study heterogeneity. A few good quality studies and systematic reviews describe moderate evidence for the utilization of therapeutic medial branch blocks and radiofrequency neurotomies in alleviating facet joint pain. Conclusion: Consequently, there is a need for high-quality cost-effectiveness studies for facet joint interventions so that evidence-based and economically viable solutions can be used to optimize patient care at a societally affordable price.